PERAN PEMERINTAH TERHADAP MASYARAKAT KORBAN KONFLIK DAN KONDISI KEHIDUPAN SOSIAL PASKA DAMAI - Mukhlis, Mukhlis; Manan, Abdul (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2021)
Jambo Keupok is a village where there was violence by the TNI against civilians and was recorded as one of the gross human rights violations during the conflict between RI-GAM. The purpose of this study was to determine the role of the government towards conflict victims and the post-peaceful social conditions of society. This research is a qualitative research by combining library research and field research. The instruments used in this study were documentation, observation, and in-depth interviews. Data analysis techniques used is the Analysis Interactive Miles and Hubermen 1994 model: data reduction, data display and conclusions. The results showed that the role of the government was to provide legal protection, reveal all perpetrators of violence against citizens and provide assistance in the form of business capital, employment and education costs to children victims of conflict. The social conditions of the conflict-affected communities in Jambo Keupok are better than before, although they are still traumatized by the incident 17 years ago, the victims' families accept it sincerely what has happened in the past and they have been carrying out their usual activities by opening small businesses in small-scale, farming, gardening and so on.